1970
DOI: 10.3329/bjn.v24i1.3036
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Prognosis of Metastatic Brain Tumour: A Study of 35 Cases

Abstract: Thirty five patients were selected to evaluate the outcome & prognosis of metastatic brain tumour in the department of Neurosurgery, Bangabandhu Sheikh Mujib Medical University, (BSMMU) Dhaka from February 2002 to December 2005. A structured questionnaire was made. Data were collected after the patient admission. All patients were evaluated with detailed history and clinical examination. MRI of Brain of these patients revealed intracranial lesions highly suspicious of metastatic brain tumour. Investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Headache and vomiting were noted as the two most common symptoms in many studies. Other symptoms noted here were also more or less similar to other studies 10,11,12,15 . But in a Polish study, the most frequent manifestation were psychic changes and neurological deficit signs (hemiperesis).…”
Section: Distribution Of the Symptomssupporting
confidence: 91%
“…Headache and vomiting were noted as the two most common symptoms in many studies. Other symptoms noted here were also more or less similar to other studies 10,11,12,15 . But in a Polish study, the most frequent manifestation were psychic changes and neurological deficit signs (hemiperesis).…”
Section: Distribution Of the Symptomssupporting
confidence: 91%
“…Debnath et al . [ 17 ] showed that the highest occupational group were day laborers (31.43%) followed by service-holders (22.85%) and farmers (20%). In our study, 29.2% of patients were day laborer followed by service holder and farmer both constituting 20.8%, which correlates with above study.…”
Section: Discussionmentioning
confidence: 99%
“…Debnath et al . [ 17 ] in their study showed that in the majority of patients with brain metastases histology of the primary was adenocarcinoma (40.00%) followed by small cell carcinoma of lungs (28.57%) and squamous cell carcinoma (22.86%). In the present study in the majority of patients histology of primary malignancy was adenocarcinoma constituting 38.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a female preponderance. The most common histologic subtype metastasizing to the brain is adenocarcinoma, followed by small cell lung carcinoma and squamous cell carcinoma (13,16,17) . Primary tumor histology remains unknown in 3 to 4% of patients (18) .…”
Section: Discussionmentioning
confidence: 99%